TRADISI KESENIAN GONDANG BOROGONGPADA MASYARAKAT DI DESA RAMBAH HILIR TENGAH KECAMATAN RAMBAH HIIR KABUPATEN ROKAN HULU - Randa, Juzi; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
At Rambah Hilir half village has a art and until now still withstand that is Gondang Borogong. This identic with a art for use at tradition events and ritual events. But with the evolution of time make this traditional art almost lost and have seldom to play by young generation. Because they apprehensive with condition of traditional art Gondang Borogong the players of Gondang Borogong unanimous to make a community of traditional art Gondang Borogong that name is Teluk Riti Art the problem that take in this research is 1. What mean of traditional art Gondang Borogong at community in Rambah Hilir half village Rambah Hilir subdistrict Rokan Hulu district. 2. What the factor that inhibit this traditional art Gondang Borogong not developing. The method that use in this research is qualitative research method. The location of this research at Rambah Hilir Half Village Rambah Hilir Subdisrtict Rokan Hulu district. That to be the subject in this research is players of Gondang Borogong that consists of peoples. One of they is owner of traditional art Gondang Borogong also as custom mamak and one other is a poeple that ever used traditional art Gondang Borogong to custom wedding event. The thecnical to accumulation data that used is live interview and documentation. Result of this research unviersally so writer can to disclose that cognition of young generation now to conserve traditional art Gondang Borogong very little this condition is proven with look the age of players Gondang Borogong that average they age are more or less thirty years and more of that.Keywords : Art, Gondang Borogong, Traditional